High Quality GaAs Epilayers Grown on Si Substrate Using 100 nm Ge Buffer Layer - Wei-Cheng Kuo; Hung-Chi Hsieh; Wu Chih-Hung; Huang Wen-Hsiang; Chien-Chieh Lee; Jenq-Yang Chang (International Journal of Photoenergy)
We present high quality GaAs epilayers that grow on virtual substrate with 100 nm Ge buffer layers. The thin Ge buffer layers were modulated by hydrogen flow rate from 60 to 90 sccm to improve crystal quality by electron cyclotron resonance chemical vapor deposition (ECR-CVD) at low growth temperature (180°C). The GaAs and Ge epilayers quality was verified by X-ray diffraction (XRD) and spectroscopy ellipsometry (SE). The full width at half maximum (FWHM) of the Ge and GaAs epilayers in XRD is 406 arcsec and 220 arcsec, respectively. In addition, the GaAs/Ge/Si interface is observed by transmission electron microscopy (TEM) to demonstrate the epitaxial growth. The defects at GaAs/Ge interface are localized within a few nanometers. It is clearly showed that the dislocation is well suppressed. The quality of the Ge buffer layer is the key of III–V/Si tandem cell. Therefore, the high quality GaAs epilayers that grow on virtual substrate with 100 nm Ge buffer layers is suitable to develop the low cost and high efficiency III–V/Si tandem solar cells.